Threonine and tyrosine kinase may serve as a prognostic biomarker for gallbladder cancer - Xie, Yuan (World J Gastroenterol, 2017)
AIM: To detect the expression of threonine and tyrosine kinase (TTK) in gallbladder cancer (GBC) specimens and analyze the associations between TTK expression and clinicopathological parameters and clinical prognosis. METHODS: A total of 68 patients with GBC who underwent surgical resection were enrolled in this study. The expression of TTK in GBC tissues was detected by immunohistochemistry. The assessment of TTK expression was conducted using the H-scoring system. H-score was calculated by the multiplication of the overall staining intensity with the percentage of positive cells. The expression of TTK in the cytoplasm and nucleus was scored separately to achieve respective H-score values. The correlations between TTK expression and clinicopathological parameters and clinical prognosis were analyzed using Chi-square test, Kaplan-Meier method and Cox regression. RESULTS: In both the nucleus and cytoplasm, the expression of TTK in tumor tissues was significantly lower than that in normal tissues (P < 0.001 and P = 0.026, respectively). Using the median H-score as the cutoff value, it was discovered that, GBC patients with higher levels of TTK expression in the nucleus, but not the cytoplasm, had favorable overall survival (P < 0.001), and it was still statistically meaningful in Cox regression analysis. Further investigation indicated that there were close negative correlations between TTK expression and tumor differentiation (P = 0.041), CA 19-9 levels (P = 0.016), T stage (P < 0.001), nodal involvement (P < 0.001), distant metastasis (P = 0.024) and TNM stage (P < 0.001). CONCLUSION: The expression of TTK in GBC is lower than that in normal tissues. Higher levels of TTK expression in GBC are concomitant with longer overall survival. TTK is a favorable prognostic biomarker for patients with GBC.